Desenvolvimento de material didático digital para o ensino de Língua Portuguesa na perspectiva de gêneros e multiletramentos - Marchezan, Mariléia da Silva (2018)
Researches in the field of Applied Linguistics identify gaps into the processes of consuming and producing multimodal genres in the elementary school (MOTTA-ROTH, 2006, 2008; HYLAND, 2003, 2007; MEURER, 2011, ROSE; MARTIN, 2012).Considering this, we need to reevaluate the Portuguese language classes due to the students’ lack of interest because most of time students act as content receptors and usually they do not produce different discursive genres. This study was carried out at the Post-Graduate Program of Networking Technologies in Education, with focus on the Development of Networking Educational Technologies, and it aims at developing digital learning material for Portuguese language in order to promote reading and writing multimodal genre production and literacies in the perspectives of genre pedagogy and multiliteracies by using digital technologies, since these are part of students’ everyday activities. To do it, our theoretical background is based on previous studies conducted in the field of Applied Linguistics (HALLIDAY, 1978; HEBERLE, 2005; FUZER, 2012; CABRAL, 2014), which consider language as a resource for meaning making. We propose an investigation divided into three moments during the Portuguese classes in a public school located in Alegrete/RS, whose students were seniors in the high school. This is an action-research and the instruments used for data collection were diagnostic, and evaluation questionnaires applied during the experiences, as well as filming, photos, reflexive diaries written by the researcher, the activities done by students in the Google Classroom. The study sought to promote practices that allow the students to assume active role during the learning process (FREIRE, 1996), and collaborative learning (KENSKI, 2000, 2008) through the use of the platform Google Classroom, and other tools powered by Google, as well as WhatsApp and Canva. The Portuguese classes were taught in a contextualized way, and it explores the multimodal genre “infographic” which can include different semiotic systems in order to develop students’ multiliteracies (COPE; KALANTZIS, 2009; 2015; ROJO, 2012; ROJO; BARBOSA, 2015; ROJO, 2016; JESUS; CARBONIERI, 2016; DIONISIO, 2008; CATTO; HENDGES, 2010; RIBEIRO, 2016) at the digital resources exploration. The questionnaires were analyzed quantitatively and qualitatively, and it allows us to elaborate the first version of the Digital Teaching Material as a hybrid course (BACICH; NETO; TREVISANI, 2015; VALENTE, 2015). The results show positive aspects related to Portuguese language teaching practice through exploring the multimodal genre infographic and the different technologies, considering the fact that participants informed that the Portuguese language activities became better and more interesting with the course application, in such a way preparing the learners to better read and to analyze multimodal genres available in different social contexts. We also verified that the genres pedagogy as proposed by Rose and Martin (2012) is a useful way to support the material design and to conduct the teaching practicing by guide the students to the processes of deconstruction of genre, the collaborative and the independent construction, with the comprehension of communicative proprieties and the compositional own characteristics of the genre as well as the collaborative and individual production of the students through the use of application such as WhatsApp, Google Docs, Google Form and Canvas, thus also enhancing the multiliteracies practice.